Analisis Faktor yang Berpengaruh Terhadap Ketidaktepatan WaktuPengembalian Berkas Rekam Medis Rawat Inap di RS X Bogor - Al Aufa, Badra (UI Scholars Hub, 2018)
The timeliness of returning medical record files (MR) in a hospital is an element that influences the quality of medical record unit performance. Based on the SOP at the Bogor X Hospital and the Government Regulation, the standard of MR return time is 2x24 hours after the patient returns. In December 2017-February 2018, the percentage of medical record files returned on > 2x24 hours is 65.54%. So this study aims to determine the factors that influence the timeliness of the MR’s return in the inpatient unit. This study uses a qualitative approach with data collection methods in depth interviews, observation and document review. As the results, the factors that influence the delay in returning BRM at the Bogor X Hospital are the limited number of staff, the distance between buildings inpatient services and medical record unit, and the lack of socialization of SOP. In order to increase effectiveness and efficiency of medical record unit services, it is necessary to periodically do monitoring and evaluating MR returns.